2021
DOI: 10.3389/fpsyg.2021.746154
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and Life Satisfaction in Spanish University Students. Effects of an Emotionally Positive and Creative Program

Abstract: There is an increasing demand by society that university students demonstrate competitive skills to enable them to achieve greater success when entering the workplace. Creativity and life satisfaction correlate positively with academic performance, productivity, and excellence in the working environment. The presence of creativity and emotional intelligence in the curriculum and teaching methods in Spanish universities, however, is surprisingly lacking. Studies that examine gender differences in these variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
(116 reference statements)
0
8
0
1
Order By: Relevance
“…As an important element in happiness, life satisfaction is the gap between what people have and what they want ( 14 ), which correlates positively with academic performance and productivity ( 15 ). It is believed that life satisfaction is affected by conditions such as health, socioeconomic status, and activities ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important element in happiness, life satisfaction is the gap between what people have and what they want ( 14 ), which correlates positively with academic performance and productivity ( 15 ). It is believed that life satisfaction is affected by conditions such as health, socioeconomic status, and activities ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that women achieved significantly higher scores in creativity and life satisfaction, which remained high even after the intervention. The findings highlight the importance of emotional and creative education in universities, as it can enhance employability and ensure equal opportunities for all students [17].…”
Section: Creativitymentioning
confidence: 87%
“…The research results found that a positive emotional and creative intervention had a more significant impact on women, highlighting the need for emotional and creative education to enhance employability and ensure equal opportunities. University students should prioritize enhancing their creativity and emotional intelligence to improve their academic and work performance, and curricula should implement interventions to unleash students' potential [17]. The research findings have revealed that certain personality traits, such as emotional stability, extraversion, and conscientiousness, play a crucial role in enhancing creativity.…”
Section: Exploring the Relationship Between Personality Traits (Emoti...mentioning
confidence: 99%
“…Therefore, life satisfaction is directly related to family satisfaction (Valdemoros San Emeterio et al, 2020) and represents one of its specific areas (Perugache Rodríguez et al, 2016). In this sense it is important to foster programs that promote better levels of self-esteem and family satisfaction to improve the levels of life satisfaction as observed in different studies (Caballero-García and Sánchez Ruiz, 2021;Lee and Tsai, 2022;Šimunović and Olčar, 2022).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%